Actors and key resources in facilitating the transition of students from one school cycle to another - Medeanu, Camelia; Moron, Nicoleta (Technium Social Sciences Journal, 2022)
Currently, many researchers are focusing on the educational environment to assess the impact of the pandemic on the educational success of pre-university or even university students. Most of the hypotheses are related to the influence of the alternative teaching methods used during the pandemic on the school results, on the socio-emotional situation and on the resources available to students and teachers to respond better to the new format of teaching and assessment in times of crisis. In this context, it is highly unlikely that the results of such studies will be interpreted in light of the challenges already existing in a pre-pandemic education system. The paper we propose brings into question exactly this general context, offering researchers a benchmark in their analyzes regarding the impact of the pandemic on the Romanian educational environment. We base our approach on the results of a qualitative research undertaken in educational institutions in the North-East Region of Romania. The research included interviewing 60 teachers, using the in-depth interview to capture the difficulties that students and teachers face in successfully ensuring the school transition. The results of our study highlight aspects related to key actors that can support the successful implementation of the school transition, existing barriers and resources needed to facilitate the school transition.